Morphological and phylogenetical analyses of pathogenic Hypomyces perniciosus isolates from Agaricus bisporus causing wet bubble disease in China - Zhang, Chun-Lan; Jin, Zheng-Wen; Sun, Can; Moodley, Odeshnee; Xu, Ji-Ze; Li, Yu (Phytotaxa, 2021)
Hypomyces perniciosus is a destructive pathogen of Agaricus bisporus. The disease has been known to occur wherever A. bisporus is cultivated. Morphological characteristics have shown differences between reported isolates of H. perniciosus. However, clarification is needed to determine whether those isolates are the same species and an investigation of the phylogenetic relationships among them is warranted. Here, taxonomic and phylogenetic studies were carried out on 29 wet bubble disease pathogen isolates from China. Our analyses of the morphological characteristics and phylogenetic results support that they are the same H. perniciosus. Moreover, they are separated into two groups, groups ⅰ and groups ii. Pathogenicity test results inferred that group ii had weaker pathogenicity than group ⅰ. Consequently, we can deduce that wet bubble disease is still caused by H. perniciosus and isolates from two distinct groups.